Revisiting the Creation Mandate 'Be Fruitful and Multiply, Fill the Earth and Subdue It' in Genesis 1:28 from an Ecotheological Perspective - Panggarra, Robi; Budiman, Sabda (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2025)
The creation mandate that God gives to humanity is encapsulated in the phrase "Be fruitful and multiply, fill the earth and subdue it" in Genesis 1:28. This command presents challenges both in terms of interpretation and application. The main issue is whether the command to "fill the earth" remains relevant to do and fulfill, and what exactly the Bible intends by this. The command to fill the earth is also accompanied by the command to "subdue it," which carries a negative connotation. The purpose of this research is to present a discussion regarding the meaning of these two commands and to analyze their relevance in the present context. The author employs a qualitative method with an exegesis approach and literature study. The findings reveal that the command to "fill" should not only be understood literally but also spiritually. Birth, in this context, should also occur spiritually through evangelism and discipleship. Furthermore, the commands to "fill" and "subdue" are closely related, emphasizing the principles of balance and stewardship. Humanity must ensure that the human population is in harmony with available resources. This also speaks to humanity's responsibility to manage creation so that resources are sufficient for all.